Assessment of mental health literacy using a multifaceted measure among a Chinese rural population - Liang Zhou; Shui-yuan Xiao; Mi Hu; Hui-ming Liu; Yu Yu; Zi-wei Liu; Xi-guang Liu; Joyce P Yang (BMJ Open)
Objectives The present study aims to assess mental health literacy (MHL) using a standardised multifaceted 20-item instrument called Mental Health Knowledge Questionnaire (MHKQ) developed by the Chinese Ministry of Health, among a rural Chinese population.Setting Four villages in Liuyang county of Hunan province, China.Participants This was a cross-sectional study. A multistage cluster-sampling method was adopted, leading to a final sampling frame of 2377 residents aged 18–60 years from four villages of Liuyang county. Included in the study were residents aged 18–60 years living in their village for at least half a year; excluded were those not living in the areas during the research period, those with difficulty in communication due to serious physical or mental illness and those who were cognitively impaired or actively psychotic. Finally, 2052 participants completed the survey.Primary and secondary outcome measures Primary outcome was correct response rate of the MHKQ; secondary outcome measures were association between sociodemographics and MHL, and association between MHL and health outcomes.Results Correct response rates for the 20 MHKQ items ranged from 19% to 94%, with a mean rate of 58%. Younger age (r=−0.02, p<0.01), higher education (r: 1.38–2.69, p<0.01) and higher income (r=0.41, p<0.01), were independently associated with higher MHL. MHL was independently associated with self-rated general health (r=2.31, p<0.01), depression (r=−0.09, p<0.01) and anxiety (r=−0.07, p<0.05).Conclusions MHL in the rural areas of Liuyang is lower than that reported in urban areas of China. There is much room for improvement with regard to MHL promotion in rural areas of China. Younger age, higher education and higher income are the three robust factors related to higher MHL, so cohort-specific educational intervention efforts may be indicated.